An ethnographic analysis of proverbs in christian films: ''the missing link" as a case study (2017)
Much scholarly research has been carried out on proverbs used in Yoruba traditional plays and films. However, little attention has been devoted to the use of proverbs in Christian films. This study, therefore, examines the use of proverbs in "The Missing Link", a Christian film produced by EVOM, a prominent Christian film producer in Nigeria in order to reveal their aesthetic and utilitarian values in religious discourse. Hymes' Ethnography of Communication was used as the theoretical framework. Fourteen proverbs, as employed in different contexts of the film were purposively selected for analysis. One major discovery is the fact that these proverbs were employed in the film to project the Yoruba socio-cultural ideologies and orientation. King Adegbite, the custodian of the people's custom and culture used 6 of the 14 proverbs captured in the film. This represents 42.8% of the total number of proverbs used in the film. The priests used 4 between themselves, which constitutes 28.5%. Chief Balogun used I, which constitutes 7.1%. Alamu and Ajadi used 3 proverbs between themselves, which constitutes 21.4% of the total number of proverbs in the film. All the proverbs used in the play were used by elderly men who are typical traditionalists. None was used by children or women. All the users of the proverbs were village dwellers, the urban dwellers represented by the missionaries did not use any proverb, instead they used quotations from the Bible, characteristic of Christians. Proverbs are a veritable mine full of the collective wisdom of the elderly people in the typical traditional Yoruba society. Contemporary Christian films producers now use them abundantly in their works to capture the indigenous local settings of their plays